Hemophagocytic Lymphohistiocytosis in Association with Primary Cutaneous Anaplastic Large Cell Lymphoma - Aneesh Basheer; Somanath Padhi; Ramesh Nagarajan; Vinoth Boopathy; Sudhagar Mookkappan; Nayyar Iqbal (Case Reports in Hematology)
Hemophagocytic lymphohistiocytosis (HLH) has a well known association with lymphomas, especially of T cell origin. Prognosis of lymphoma associated HLH is very poor, especially in T cell lymphomas; and, therefore, early diagnosis might alter the outcome. Though association of HLH with systemic anaplastic large cell lymphoma (ALCL) is known, its occurrence in primary cutaneous ALCL (C-ALCL) is distinctly rare. We aim to describe a case of C-ALCL (anaplastic lymphoma kinase (ALK)−) in an elderly male who succumbed to the complication of associated HLH, which was possibly triggered by coexistent virus infection. We briefly present the literatures on lymphoma associated HLH and discuss the histopathological differentials of cutaneous CD30+ lymphoproliferative disorders. We do suggest that HLH may pose diagnostic challenges in the evaluation of an underlying lymphoma and hence warrants proper evaluation for the underlying etiologies and/or triggering factors.